Identifying the effect of election closeness on voter turnout: evidence from Swiss referenda - Bursztyn, L; Cantoni, D; Funk, P; Schönenberger, F; Yuchtman, N (Oxford University Press, 2023)
We provide evidence of a causal effect of anticipated election closeness on voter turnout, exploiting the precise day-level timing of the release of Swiss national poll results for high-stakes federal referenda, and a novel dataset on daily mail-in voting for the canton of Geneva. Using an event study design, we find that the release of a closer poll causes voter turnout to sharply rise immediately after poll release, with no differential pre-release turnout levels or trends. We provide evidence that polls affect turnout by providing information shaping beliefs about closeness. The effects of close polls are the largest where newspapers report on them most; and, the introduction of polls had significantly larger effects in politically unrepresentative municipalities, where locally available signals of closeness are less correlated with national closeness. We then provide evidence that the effect of close polls is heterogeneous, with an asymmetric effect leading to a higher vote share for the underdog. The effect sizes we estimate are large enough to flip high-stakes election outcomes under plausible counterfactual scenarios.